The Role of Information Construction in Second Language Learning - Corbeil, Giselle (Linguistica Atlantica, 1992)
This article describes the second phase of a three-phase study designed to teach less successful second language students a set of effective strategies used by successful students. The first phase consisted of identifying strategies used by successful students in their response to information contained in teacher's corrective feedback. A closer analysis of the successful students' protocols has revealed the effectiveness of some strategies1 in terms of learning compared to others and hinted at the feasibility of finding a scale of 'constructive' processes ranging from low to high levels of information construction. This paper describes the various steps taken towards the elaboration of such a scale. It is suggested that the lack of constructive processing engaged in by average and below average students may affect their progress in attaining linguistic proficiency